The ALOMAR Rayleigh/Mie/Raman lidar: objectives, configuration, and performance - von Zahn, U.; von Cossart, G.; Fiedler, J.; Fricke, K. H.; Nelke, G.; Baumgarten, G.; Rees, D.; Hauchecorne, A.; Adolfsen, K. (Annales Geophysicae, 2000)
We report on the development and current capabilities of the ALOMAR Rayleigh/Mie/Raman lidar. This instrument is one of the core instruments of the international ALOMAR facility, located near Andenes in Norway at 69°N and 16°E. The major task of the instrument is to perform advanced studies of the Arctic middle atmosphere over altitudes between about 15 to 90 km on a climatological basis. These studies address questions about the thermal structure of the Arctic middle atmosphere, the dynamical processes acting therein, and of aerosols in the form of stratospheric background aerosol, polar stratospheric clouds, noctilucent clouds, and injected aerosols of volcanic or anthropogenic origin. Furthermore, the lidar is meant to work together with other remote sensing instruments, both ground- and satellite-based, and with balloon- and rocket-borne instruments performing in situ observations. The instrument is basically a twin lidar, using two independent power lasers and two tiltable receiving telescopes. The power lasers are Nd:YAG lasers emitting at wavelengths 1064, 532, and 355 nm and producing 30 pulses per second each. The power lasers are highly stabilized in both their wavelengths and the directions of their laser beams. The laser beams are emitted into the atmosphere fully coaxial with the line-of-sight of the receiving telescopes. The latter use primary mirrors of 1.8 m diameter and are tiltable within 30° off zenith. Their fields-of-view have 180 µrad angular diameter. Spectral separation, filtering, and detection of the received photons are made on an optical bench which carries, among a multitude of other optical components, three double Fabry-Perot interferometers (two for 532 and one for 355 nm) and one single Fabry-Perot interferometer (for 1064 nm). A number of separate detector channels also allow registration of photons which are produced by rotational-vibrational and rotational Raman scatter on N2 and N2+O2 molecules, respectively. Currently, up to 36 detector channels simultaneously record the photons collected by the telescopes. The internal and external instrument operations are automated so that this very complex instrument can be operated by a single engineer. Currently the lidar is heavily used for measurements of temperature profiles, of cloud particle properties such as their altitude, particle densities and size distributions, and of stratospheric winds. Due to its very effective spectral and spatial filtering, the lidar has unique capabilities to work in full sunlight. Under these conditions it can measure temperatures up to 65 km altitude and determine particle size distributions of overhead noctilucent clouds. Due to its very high mechanical and optical stability, it can also employed efficiently under marginal weather conditions when data on the middle atmosphere can be collected only through small breaks in the tropospheric cloud layers. Key words: Atmospheric composition and structure (aerosols and particles; pressure · density · and temperature; instruments and techniques)